PERJANJIAN JUAL BELI TANAH DI BAWAH TANGAN (STUDI KASUS PUTUSAN NOMOR 1233/Pdt.G/2020/PN Sby) - Sukwanto, Johan Hari (Lex Journal: Kajian Hukum & Keadilan, 2022)
Land as part of the earth's surface, has a very important meaning in human life, either as a place or a living space with all its activities, as a source of life, even for a nation, land is a territorial element in the sovereignty of the state. By law, the position of the first inhabitant is recognized as the owner. One of the acquisitions of land for humans is obtained from agreements, namely by transferring land rights that can be done through buying and selling. In carrying out this sale and purchase, the seller and buyer will make a land sale and purchase agreement, so that there will be a transfer of land rights based on what has been promised by the parties. This study aims to determine the responsibility of the parties in the sale and purchase under the hand, to find out the position of the agreement under the hand in the land sale and purchase agreement, and to find out the form of legal protection for the parties in the land sale and purchase agreement based on decision Number 1233 / Pdt.G / 2020 / PN Sby. This type of research is normative lawresearch research using normative case studies in the form of legal behavior products. Normative legal research is research conducted to collect and analyze secondary data. Data sources obtained only secondary data, namely books, diaries, laws and regulations, court decisions, legal theories and opinions of leading legal scholars. In this agreement there is an element of error on the part of the seller because the selling party (defendant I) cannot be found to exist and does not help the buyer (plaintiff) to enter into an agreement at the Notary as it should be. The underhand land sale and purchase agreement has only formal evidentiary power. So efforts are needed to provide protection to each party. Keywords: law, land, agreement, sale and purchase, rights